Testing for concordance between predicted species richness, past prioritization, and marine protected area designations in the western Indian Ocean - McClanahan, Tim R.; Friedlander, Alan M.; Wickel, Julien; Graham, Nicholas A. J.; Bruggemann, J. Henrich; Guillaume, Mireille M. M.; Chabanet, P.; Porter, Sean; Schleyer, Michael H.; Azali, M. Kodia; Muthiga, N. A. (Conservation biology, 2024)
Scientific advances in environmental data coverage and machine learning algorithms have improved the ability to make large‐scale predictions where data are missing. These advances allowed us to develop a spatially resolved proxy for predicting numbers of tropical nearshore marine taxa. A diverse marine environmental spatial database was used to model numbers of taxa from ∼1000 field sites, and the predictions were applied to all 7039 6.25‐km2 reef cells in 9 ecoregions and 11 nations of the western Indian Ocean. Our proxy for total numbers of taxa was based on the positive correlation (r2 = 0.24) of numbers of taxa of hard corals and 5 highly diverse reef fish families. Environmental relationships indicated that the number of fish species was largely influenced by biomass, nearness to people, governance, connectivity, and productivity and that coral taxa were influenced mostly by physicochemical environmental variability. At spatial delineations of province, ecoregion, nation, and strength of spatial clustering, we compared areas of conservation priority based on our total species proxy with those identified in 3 previous priority‐setting reports and with the protected area database. Our method identified 119 locations that fit 3 numbers of taxa (hard coral, fish, and their combination) and 4 spatial delineations (nation, ecoregion, province, and reef clustering) criteria. Previous publications on priority setting identified 91 priority locations of which 6 were identified by all reports. We identified 12 locations that fit our 12 criteria and corresponded with 3 previously identified locations, 65 that aligned with at least 1 past report, and 28 that were new locations. Only 34% of the 208 marine protected areas in this province overlapped with identified locations with high numbers of predicted taxa. Differences occurred because past priorities were frequently based on unquantified perceptions of remoteness and preselected priority taxa. Our environment–species proxy and modeling approach can be considered among other important criteria for making conservation decisions. Evaluación de la concordancia entre la riqueza de especies pronosticada, priorizaciones pasadas y la designación de áreas marinas protegidas en el oeste del Océano Índico Resumen Los avances científicos en la cobertura de datos ambientales y los algoritmos de aprendizaje automatizado han mejorado la capacidad de predecir a gran escala cuando hacen falta datos. Estos avances nos permiten desarrollar un representante con resolución espacial para predecir la cantidad de taxones marinos en las costas tropicales. Usamos una base de datos espaciales de diversos ambientes marinos para modelar la cantidad de taxones a partir de ∼1000 sitios de campo y aplicamos las predicciones a las 7039 celdas arrecifales de 6.25‐km2 en nueve ecorregiones y once países del oeste del Océano Índico. Nuestro representante para la cantidad total de taxones se basó en la correlación positiva (r2=0.24) de la cantidad de taxones de corales duros y cinco familias de peces arrecifales con diversidad alta. Las relaciones ambientales indicaron que el número de especies de peces estuvo influenciado principalmente por la biomasa, la cercanía a las personas, la gestión, la conectividad y la productividad y que los taxones de coral estuvieron influenciados principalmente por la variabilidad ambiental fisicoquímica. Comparamos la prioridad de las áreas de conservación a nivel de las delimitaciones espaciales de provincia, ecorregión, nación y fuerza del agrupamiento espacial basado en nuestro total de especies representantes con aquellas especies identificadas en tres reportes previos de establecimiento de prioridades y con la base de datos de áreas protegidas. Con nuestro método identificamos 119 localidades aptas para tres cantidades de taxones (corales duros, peces y su combinación) y cuatro criterios de delimitación espacial (nación, ecorregión, provincia y grupo de arrecifes). Las publicaciones previas sobre el establecimiento de prioridades identificaron 91 localidades prioritarias de las cuales seis fueron identificadas por todos los reportes. Identificamos doce localidades que se ajustan a nuestros doce criterios y se correspondieron con tres localidades identificadas previamente, 65 que se alinearon con al menos un reporte anterior y 28 que eran nuevas localidades. Sólo 34% de las 208 áreas marinas protegidas en esta provincia se traslaparon con localidades identificadas con un gran número de taxones pronosticados. Hubo diferencias porque en el pasado se priorizaba frecuentemente con base en las percepciones no cuantificadas de lo remoto y prioritario de los taxones preseleccionados. Nuestra especie representante del ambiente y nuestra estrategia de modelo pueden considerarse entre otros criterios importantes para tomar decisiones de conservación.